Cartographic Explorations of Self in Michael Ondaatje's Running in the Family and Jacques Poulin's Volkswagen Blues - Pedri, Nancy (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2008)
Shaped by both those who make and read them, maps generate a two-way transformative process whereby subjective imagination inscribes and re-inscribes place with meaning and, at the same time, prompts the subject to figure and re-configure portrayals of self as reflected in the charting of place. This enactment of the sociology of the map is particularly evident in Running in the Family by Michael Ondaatje and Volkswagen Blues by Jacques Poulin. Both texts provoke an awareness of the close connection between the representation of space and the process of mapping space on the one hand, and the intimate quest for personal and cultural identity on the other.